Layanan Praktek Konseling Komunitas - Nursyahbani, Rahmi; Day, Vania Maovangi; Miharja, Sugandi; Kusnawan, Aep (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The urgency of community counseling practice services has increased along with the growing social challenges that directly impact community well-being. Through needs assessment, outreach, mentoring, training, and the strengthening of social networks, counseling programs can help communities identify the issues they face while encouraging active participation in seeking solutions. Therefore, community counseling practice becomes an essential component in creating healthier, more inclusive, and socially responsive environments. This study employs a qualitative approach, with primary data sources derived from library research. The findings indicate that community counseling practice services represent a psychosocial service approach oriented toward empowerment, prevention, and the strengthening of individual and group capacities within a community. Community counseling does not focus solely on resolving personal problems, but also addresses social, environmental, cultural, and structural factors that influence community well-being. Through community counseling practices, communities are supported in building self-reliance, increasing social awareness, strengthening problem-solving skills, and fostering cooperation among community members.